Research Paper Socioeconomic status and survey of ethno medicinal plants used by the snake charmers of Bankura District, West Bengal, India. - Mondal, Rajendra Prasad; Dhua, Biswaranjan; Kundu, Sukanya; Chakraborty, Puja; Mandi, Rimil; Rakshit, Mahadeb; Murmu, Baren; Rakshit, Pijush (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The present work is an attempt to understand the socio economic status of snake charmer and document thetraditional uses of neglected plants as medicine in domestic livelihood system against many diseases. Thesurvey was carried out among snake charmer of Kamladanga village of Bankura District, West Bengal, Indiaduring November 2015 to January, 2016. A total of 54 individuals (18-70years) were interviewed during thesurvey including snake charmers’ wives. Due to governmental support and help, socioeconomic status ofsnake charmer’s is slightly improved as a result of shifting from their traditional profession to otherprofessions. A total of twelve (12) poisonous and non poisonous snake and 20 local plants from 12 familieswere documented. Due to increase in modern healthcare facilities and awareness , traditional ethno medicinaltreatment decreases rapidly. So proper documentation of such unique and indigenous, traditional knowledge isnecessary before it lost forever.